Chavismo and Venezuelan Foreign Policy Against the United States During 2013-2019 - Hendra Maujana Saragih; Muhammad Fikri Matdoan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This work desribe Chavismo as a populist movement and in making Venezuelan foreign policy directed towards the United States in the six years from 2013-2019. By using the Foreign Policy Theory which explains the function and purpose of foreign policy, it is found that Chavismo does not have much influence in making foreign policy towards the United States. The death of Hugo Chávez plus the poor economic conditions in the Maduro era, inevitably the problem of existence now plagues Chavismo. Chavismo under the government of Nicholás Maduro is in an alarming position. Where the position of this socialist movement no longer occupies a significant number as when Chávez, was still alive. The study of Chavismo in foreign policy is still possible given that Nicholás Maduro is a Chavista. Nicholás Maduro also carries out foreign policy with Chávez,s foreign policy. Sticking to the existing foreign policy, there is not much Maduro can do to maintain his power and the Bolivarian Revolution in Venezuela